HUBUNGAN MOTIVASI BELAJAR DENGAN PERENCANAAN KARIR KELAS FASE F (KELAS XI) DI SMA N 1 SIKABAU - Apriandes, Elisa; Adison, Joni; Suryadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the observation that some students at SMA N 1 Sikabau still exhibit low learning motivation and lack well-developed career plans. This situation is evidenced by students who frequently procrastinate on assignments, lack enthusiasm for learning, have not yet identified their interests and talents, and lack clear career goals. The study aims to describe the learning motivation and career planning of Grade XI students at SMA N 1 Sikabau and to examine the relationship between these two variables. A quantitative approach utilizing a descriptive-correlational method was employed. The study population consisted of 50 Grade XI students at SMA N 1 Sikabau, and a total sampling technique was used to include all 50 students in the sample. Data were collected via questionnaires and analyzed using descriptive statistics and the Pearson Product Moment correlation, with the assistance of IBM SPSS Statistics software (version 32.0). The results indicate that student learning motivation falls into the high, while career planning also falls into the high. The correlation analysis yielded a coefficient (r) of 0.615 (indicating a strong relationship) with a significance value of < 0.001. Thus, there is a positive and significant relationship between learning motivation and career planning among Grade XI students at SMA N 1 Sikabau. Consequently, it is recommended that guidance and counseling teachers, as well as subject teachers, provide services and materials designed to elevate both learning motivation and career planning from the "high" category to the "very high" category.